Aerodynamic optimization of HandiHaler and Respimat: the roles of computational fluid dynamics and flow visualization - Wachtel, Herbert; Ertunc, Özgür; Köksoy, Cagatay; Delgado, Antonio (Respiratory Drug Delivery 2008 (2008), 2008)
UnivIS-Import:2015-04-16:Pub.2008.tech.ITC.stmmec.aerody_1

Alteration of power spectra of velocity fluctuations in a turbulent round jet flow - Köksoy, Cagatay; Ertunc, Özgür; Delgado, Antonio; Derlien, Hans (8 EFMC, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.ITC.stmmec.altera

A method for the aerodynamic design of dry powder inhalers - Ertunc, Özgür; Köksoy, Cagatay; Wachtel, Herbert; Delgado, Antonio (International Journal of Pharmaceutics, 2011)
An inhaler design methodology was developed and then used to design a new dry powder inhaler (DPI) which aimed to fulfill two main performance requirements. The first requirement was that the patient should be able to completely empty the dry powder from the blister in which it is stored by inspiratory effort alone. The second requirement was that the flow resistance of the inhaler should be geared to optimum patient comfort. The emptying of a blister is a two-phase flow problem, whilst the adjustment of the flow resistance is an aerodynamic design problem. The core of the method comprised visualization of fluid and particle flow in upscaled prototypes operated in water. The prototypes and particles were upscaled so that dynamic similarity conditions were approximated as closely as possible. The initial step in the design method was to characterize different blister prototypes by measurements of their flow resistance and particle emptying performance. The blisters were then compared with regard to their aerodynamic performance and their ease of production. Following selection of candidate blisters, the other components such as needle, bypass and mouthpiece were dimensioned on the basis of node-loop operations and validation experiments. The final shape of the inhaler was achieved by experimental iteration. © 2011 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.ametho
Keywords: Design; DPI; Dry powder; Flow visualization; Fluid mechanics; Inhaler

An analytical model for droplet separation in vane separators and measurements of grade efficiency and pressure drop - Koopmann, Hans K.; Köksoy, Cagatay; Ertunc, Özgür; Lienhart, Hermann; Hedwig, Heinz-Jürgen; Delgado, Antonio (Nuclear Engineering and Design, 2014)
This study investigates the predictive power of analytical models for the droplet separation efficiency of vane separators and compares experimental results of two different vane separator geometries. The ability to predict the separation efficiency of vane separators simplifies their design process, especially when analytical research allows the identification of the most important physical and geometrical parameters and can quantify their contribution. In this paper, an extension of a classical analytical model for separation efficiency is proposed that accounts for the contributions provided by straight wall sections. The extension of the analytical model is benchmarked against experiments performed by Leber (2003) on a single stage straight vane separator. The model is in very reasonable agreement with the experimental values. Results from the analytical model are also compared with experiments performed on a vane separator of simplified geometry (VS-1). The experimental separation efficiencies, computed from the measured liquid mass balances, are significantly below the model predictions, which lie arbitrarily close to unity. This difference is attributed to re-entrainment through film detachment from the last stage of the vane separators. After adjustment for re-entrainment effects, by applying a cut-off filter to the outlet droplet size spectra, the experimental and theoretical outlet Sauter mean diameters show very good agreement. A novel vane separator geometry of patented design (VS-2) is also investigated, comparing experimental results with VS-1. Experimental separation efficiencies based on recorded mass flow balances are very similar for both geometries. However, based on an analysis of the outlet droplet size spectra, VS-2 outperforms VS-1. It is concluded that re-entrainment effects cloud the performance of VS-2 and that the perforations in the wall sections of VS-2 are not very effective. Pressure drop measurements performed on both geometries reveal that the pressure drop for VS-2 is higher than for VS-1 by a factor of almost two for gas velocities up to 10 m/s. © 2014 Elsevier B.V.
UnivIS-Import:2015-04-14:Pub.2014.tech.ITC.stmmec.ananal

Experimental investigation of particle deagglomeration using turbulence - Köksoy, Cagatay; Ertunc, Özgür; Hüttner, Sebastian; Wachtel, Herbert; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The effect of turbulence on powder aerosol deagglomeration was investigated. Two impinging jets were used to generate turbulence. Lactose particles, whose fully dispersed fine particle fraction (FPF) - number percentage of the particles whose diameter smaller than 5 μm- is above 90 %, were applied as aerosol powder. The particle size distribution after the dispersion unit were measured by using phase Doppler anemometer (PDA) and turbulence level were quantified at the impingement point of two jets with laser Doppler anemometer. As the turbulence level increases turbulent time and length scales decrease, and the ratio of fine particle fraction (FPF) increases from 36% to 86%.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.experi_1

Numerical simulations of swirling pipe flows - decay of swirl and occurrence of vortex structures - Vaidya, Haresh Anant; Ertunc, Özgür; Genc, Balkan; Beyer, Florian; Köksoy, Cagatay; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The present work aims at better understanding of the physics underlying swirling flows in pipes by means of numerical simulations. Direct numerical simulations have been carried out by using two different inlet swirl conditions. In one case, rotating honeycomb is used as the means to generate swirl whereas in the other case a solid body rotation is provided at the inlet. The inlet swirl intensity is varied in order to scan the underlying physics. Reynolds number 1730 is selected so that the flow remains in laminar regime. The results are compared with those obtained from the experiments using a similar experimental set-up. It is shown that the increase in the inlet swirl intensity leads to a faster decay of swirl downstream of the pipe. Similarly certain specific vortex structures are observed in the radial velocity contours. These structures are thought to be analogous with those found in the Taylor-Couette flow between a stationary outer cylinder and inner rotating cone. The reported investigations reveal dependence of swirl decay on the inlet swirl intensity and occurrence of vortex structure

Numerical simulations of swirling pipe flows- decay of swirl and occurrence of vortex structures - Vaidya, Haresh Anant; Ertunc, Özgür; Genc, Balkan; Köksoy, Cagatay; Beyer, Florian; Delgado, Antonio (Journal of Physics : Conference Series, 2011)
The present work aims at better understanding of the physics underlying swirling flows in pipes by means of numerical simulations. Direct numerical simulations have been carried out by using two different inlet swirl conditions. In one case, rotating honeycomb is used as the means to generate swirl whereas in the other case a solid body rotation is provided at the inlet. The inlet swirl intensity is varied in order to scan the underlying physics. Reynolds number 1730 is selected so that the flow remains in laminar regime. The results are compared with those obtained from the experiments using a similar experimental set-up. It is shown that the increase in the inlet swirl intensity leads to a faster decay of swirl downstream of the pipe. Similarly certain specific vortex structures are observed in the radial velocity contours. These structures are thought to be analogous with those found in the Taylor-Couette flow between a stationary outer cylinder and inner rotating cone. The reported investigations reveal dependence of swirl decay on the inlet swirl intensity and occurrence of vortex structures.
UnivIS-Import:2015-04-14:Pub.2011.tech.ITC.stmmec.numeri_5

Visuelle Untersuchung turbulenter Jet-Strömung unter passiver Beeinflussung - Ertunc, Özgür; Derlien, Hans; Köksoy, Cagatay; Delgado, Antonio (Proceedings der 20. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.ITC.stmmec.visuel